Bridging the Gap: Critical Thinking Practices for History Educators in Private Secondary Schools of Marawi City, Philippines - Daud, Khalid; Dimasira , Alinaib; Imam , Hassanor; Lao, Faisah (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
The study examines the teaching strategies used by history educators in private secondary schools in Marawi City, Lanao del Sur, Philippines, focusing on fostering critical thinking among students. History education often encounters the challenge of being perceived as monotonous, primarily due to traditional teaching methods emphasizing rote memorization. This research aims to explore innovative and inclusive approaches to teaching history, encouraging curiosity, critical analysis, and active participation. Utilizing a descriptive research design, data were gathered through surveys and interviews with history teachers to analyze their methods and assess their effectiveness in enhancing student learning. The findings reveal that interactive teaching strategies, technological integration, and diverse historical resources positively influence students’ engagement and critical thinking abilities. Despite these advances, challenges persist, particularly in the accessibility of resources and the availability of professional training for educators. The study highlights the necessity of equipping history educators with adequate tools and training to deliver engaging and impactful lessons. Key recommendations include organizing professional development programs, updating curricula to include collaborative and inquiry-based learning models, and ensuring access to comprehensive teaching resources. This research contributes to the ongoing efforts to improve history education and provides valuable insights for future studies aimed at refining pedagogical practices in this field.